Die rhythmischen Martinsschriften Guiberts von Gembloux (BHL 5636/5637) - Wibert von Gembloux, Abt 1124-1213 (Brill, 2017)
"Martin of Tours is one of the most popular saints of the Middle Ages and, accordingly, his hagiographical afterlife is tremendously rich. In the twelfth century, Martinian studies flourished again and Guibert of Gembloux (d. 1213) was an outstanding collector of ancient and modern material about his favourite patron, which he used as a basis for various works of his own. In the centre of this biographical and didactical project Guibert placed two rhythmical poems, which he dedicated to the life of Martin (Libellus panegericus) and an impressive series of his venerators (Libellus de specialibus piissimi patroni veneratoribus). In this book Peter Orth provides the first critical edition of both poems with about 12,000 rhythmical lines, together with an introduction, commentary and indices."--
Keywords: Wibert -- von Gembloux, Abt -- 1124-1213 -- Libellus de specialibus piissimi patroni veneratoribus; Wibert -- von Gembloux, Abt -- 1124-1213 -- Libellus panegyricus in sanctum Martinum; Martin -- Tours, Bischof, Heiliger -- 316-397; Martin / Saint, Bishop of Tours / approximately 316-397; Martin / Saint, Bishop of Tours / approximately 316-397 / Poetry; Guibert / de Gembloux, Abbot of Gembloux / approximately 1125-1213; Poetry; Kommentar